Diagnostic performance of 256-row detector coronary CT angiography in patients with high heart rates within a single cardiac cycle: a preliminary study. Issue 8 (August 2017) - Liang, J.; Wang, H.; Xu, L.; Yang, L.; Dong, L.; Fan, Z.; Wang, R.; Sun, Z.
Abstract : Aim: To evaluate the image quality and diagnostic performance of coronary computed tomography angiography (CCTA) in patients with high heart rate within a single cardiac cycle using a 256-row detector CT system. Materials and methods: Eighty-four consecutive symptomatic patients (mean age 60.4±9.1 years, 52 men) with suspected coronary artery disease and heart rate ≥75 beats/min undergoing CCTA and invasive coronary angiography (ICA) were enrolled retrospectively. Prospective electrocardiography (ECG)-triggered volume CCTA within a single cardiac cycle was performed using a 256-row, 16 cm detector CT system (Revolution CT, GE Healthcare) using automated tube voltage selection (kV Assist selecting 100 or 120 kV) and tube current modulation (Smart mA) techniques, with images reconstructed using 50% of adaptive statistical iterative reconstruction-V (ASiR-V). The image quality of coronary artery segments was evaluated by two reviewers using a four-point scale based on 18-segment model. The diagnostic accuracy of CCTA to detect ≥50% stenosis on ICA was analysed. The sensitivity, specificity, positive predictive value, and negative predictive value of CCTA to detect a ≥50% diameter stenosis on ICA were calculated from the chi-squared test of the contingency table on a per-segment, per-vessel, and per-patient basis. Results: The body mass index was 25.6±3.5 kg/m 2 ; the HR was 82.8±7.9 beats/min, and the mean HR variability was 8.3±4.8 beats/min. All of the coronary artery segments, 98.9% (1044/1056) of coronary segments were rated as having diagnostic image quality. The diagnostic sensitivity, specificity, positive predictive value, and negative predictive value of CCTA, were 91.5%, 95.6%, 77.7%, and 98.5% on a per-segment basis; 95.2%, 93.5%, 87%, and 97.7% on a per-vessel basis; 100%, 85.7%, 93.3%, and 100% on per-patient basis, respectively. The mean effective dose was 1.9±1 mSv. Conclusions: CCTA using a 256-detector row CT with the snapshot freeze (SSF) technique can be performed in a single cardiac cycle with acquisition of images with high diagnostic value and low radiation dose in patients with high heart rates. Highlights: Patient with heart rate≥75bpm can be performed in one beat using 256-row detector CT. Coronary CT angiography with snapshot freeze can acquire high image quality. Coronary CT angiography with snapshot freeze in patient with high heart rate can acquire high diagnostic accuracy. The mean effective dose of coronary CT angiography was low than 2.0 mSv.